2017
DOI: 10.5116/ijme.5951.6044
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing virtues of the medical profession: does it enhance medical students’ empathy?

Abstract: ObjectivesTo examine if the empathy levels of first-year medical students are amenable to didactic interventions idealized to promote values inherent to medical professional identity. MethodsThis is a pretest-posttest study designed to assess the empathy levels of first-year medical students (n=166) comprising two consecutive classes of a Brazilian medical school, performed before and after a didactic intervention. Students attended a course based on values and virtues related to medical professional identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…The ‘explicit’ professionalism curriculum puts patients into the center and supports altruistic attitudes, but the ‘implicit’ or ‘hidden’ curriculum that is defined by the learning environment in which it takes place ( Hafferty and Franks, 1994 ) is often contrary, e.g., educators teaching opposite values by valuing appearance, formality, and conformity wrongly as ‘professional’ ( Brainard and Brislen, 2007 ; Karches and Sulmasy, 2016 ). However, medical students’ altruistic behavior and empathy seem to be susceptible ( Schweller et al, 2017 ; Sanjai and Gopichandran, 2018 ) and should be fostered by respective early curricular interventions during medical education.…”
Section: Virtues and Character Strengths In The Literaturementioning
confidence: 99%
“…The ‘explicit’ professionalism curriculum puts patients into the center and supports altruistic attitudes, but the ‘implicit’ or ‘hidden’ curriculum that is defined by the learning environment in which it takes place ( Hafferty and Franks, 1994 ) is often contrary, e.g., educators teaching opposite values by valuing appearance, formality, and conformity wrongly as ‘professional’ ( Brainard and Brislen, 2007 ; Karches and Sulmasy, 2016 ). However, medical students’ altruistic behavior and empathy seem to be susceptible ( Schweller et al, 2017 ; Sanjai and Gopichandran, 2018 ) and should be fostered by respective early curricular interventions during medical education.…”
Section: Virtues and Character Strengths In The Literaturementioning
confidence: 99%
“…There have been many studies utilizing JSPE score to assess empathy levels in healthcare students or professionals, although these have found mixed results. Systematic reviews have found that physician empathy appears to be an important aspect of patient and physician well-being, and targeted educational programs may significantly enhance the empathy levels of medical students and physicians [1115]. However, other studies have demonstrated that brief interventions did not lead to significant increases in empathy [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Seoane and colleagues’ (2016) National Institutes of Health study demonstrates that a simple in-class intervention (15 hours of content regarding the application of medical virtues in a clinical context) diminished the loss of empathy and “burnout” that accompany students’ journeys through medical school. Another recent study bolstered these results by demonstrating that a virtues-based pedagogic approach (through a mixture of in-class and real-world interventions) increased students’ empathy towards patients and, in doing so, enhanced their professional practice and developing identities ( Schweller, Ribeiro, Celeri, & de Carvalho-Filho, 2017 ).…”
Section: Virtues and Professional Educationmentioning
confidence: 98%